Immunity in the first year of life and call for vaccination - Shewale, Sunil; Parekh, Sameer (International Journal of Biological Research, 2014)
Children present special needs because of their vulnerability and developmental peculiarities. Early stage protection is critical in children and the immunization in the first year is especially important. Hence to protect them against some of the most dangerous diseases during and beyond the first year of life, it is essential that infants should get all recommended vaccines at the right time. The vaccines work by building up the child's defense mechanism against diseases. Some vaccines require multiple doses for full protection and every child thus, must complete particular immunization schedule. A child who is not immunized is more likely to become sick, permanently disabled or undernourished, and could possibly die. This article explores the current knowledge about the importance of immunity before and after the beginning of human life and reviews the essential vaccines for infancy. It will ultimately help to explore science of immunology and vaccinology. Keywords: Infants, Infectious Diseases, Immunity, Immunization, Vaccine.